Interactions of Human- and Rat-Organic Anion Transporters With Pravastatin and Cimetidine - Suparat Khamdang; Michio Takeda; Minoru Shimoda; Rie Noshiro; Shinichi Narikawa; Xiu-Lin Huang; Atsushi Enomoto; Pawinee Piyachaturawat; Hitoshi Endou (Elsevier, 2004)
We have elucidated the interactions of human and rat organic anion transporters (hOATs and rOATs) with pravastatin and cimetidine. Pravastatin inhibited hOAT1/rOAT1, hOAT2/rOAT2, hOAT3/rOAT3, and hOAT4. The mode of inhibition was noncompetitive for hOAT1 and hOAT2, whereas it was competitive for hOAT3 and hOAT4. Cimetidine also inhibited hOAT1/rOAT1, hOAT3/rOAT3, and hOAT4. The mode of inhibition was a combination of competitive and noncompetitive manners for hOAT1, whereas it was competitive for hOAT3. The effects of OAT inhibitors on OAT1, OAT2, and OAT3 exhibited some but not so remarkable interspecies differences between humans and rats. In conclusion, we have characterized pravastatin and cimetidine as OAT inhibitors. Keywords:: organic anion transporter, pravastatin, cimetidine